Design of Catamaran Propulsion System with Demihull Distance Variation on Hospital Ship - Amiadji; Agoes Santoso; Bondan Al Akbar Sabastian (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
Various problems faced by health services in the area of remote islands based on survey data Ministry of Health, that limited human resources in health and treatment facilities, as well as the difficult geographical conditions causing problems transport and communication are the main problem. From the above, the problems faced by means of a mobile hospital in the form of vessels operating from one small island to another small island is the solution of health problems for the people living within the island of Madura. In this thesis the work will be done planning catamaran ship propulsion system with a variety of distances and determine the power demihull hospital equipment. From the calculation results in a variation within demihull get with B = 19.51 m, 0,1B = 21.46, 0,2B = 23.41, 25.36 resulting 0,3B = 97.8 kN after the engine power of 812.71 kW obtained. From the selection of the engine 10 criteria obtained type Caterpillar 3508B engines. Power generators are required for a hospital ship is 75kW for 4 gensets.